The crystal and molecular structures of some transition metal-barbiturate complexes - Rodgers, Allen Lawrence (Department of Chemistry, 2016)
This thesis describes the synthesis and X-ray structural investigation of four complexes of the type M(II)(barb)₂L₂ where M is a transition metal, barb is the anion of a substituted barbituric acid and L is an organic base. These compounds are of importance in the clinical detection and identification of barbiturate drugs and this aspect is discussed in a later section. An infrared study of these compounds is also described. The individual components of the complexes, viz. the transition metals and the barbiturate ligands are in themselves of great biological and physiological significance. Although the human body is but 3% metals, life depends upon these elements far more than this figure suggests. For example, the transition series metals, even though some are present in only trace amounts, generally appear in the active centres of enzymes that catalyze substrates to form aggregate molecules. The barbiturates on the other hand are members of a group of widely used drugs known as hypnotics, many of which are medicinally applied today.